Diversifikasi dan Pemasaran Berbasis E-Commerce Produk Kopi Desa Harapan Kab. Barru Sulawesi Selatan Menuju Desa Wirausaha Mandiri - Subariyanto Subariyanto; Ernawati Syahruddin Kaseng; Rika Riwayani; Firdaus W. Suhaeb; Syarifah Suryana (DEDIKASI, 2026)
Abstract. E-Commerce Based Diversification and Marketing Training for Coffee Products in Harapan Village, Barru Regency, South Sulawesi Towards a Mandi Entrepreneurial Village is a strategic effort made to improve the understanding and skills of coffee farmers in handling post-harvest coffee. In the early stages of Community Service (PKM) activities, it was found that coffee farmers in Harapan Village, Tanete Riaja District, did not have in-depth knowledge about post-harvest coffee handling and obstacles in the marketing system. Based on the results of the initial stage of observation, the solution carried out was to carry out a field assessment related to the analysis of the situation at the farmer level, organize farmers and provide training on post-harvest coffee handling. The methods of activities provided include: (1) direct observation method, (2) structured interview method, (3) lecture method, simulation, (4) open discussion method and also provide a module for handling post-harvest coffee as well as conducting evaluation and monitoring. The results of post-harvest coffee training activities have a positive impact on increasing the knowledge of coffee farmers in Harapan Village, which can be seen from the results of the pre-test 5.45% and post-test results of 8.27%. The results of the evaluation and monitoring carried out after 1 month of training activities, it is known that coffee farmers in Harapan Village have carried out post-harvest coffee activities, especially downstream processing of coffee beans. The conclusion of the coffee post-harvest training activity in Harapan village is the increase in knowledge and skills and the commitment of coffee farmers in post-harvest coffee activities. Keywords: Diversification; Marketing; Independent Village and E-Commerce